Efetividade da auriculoterapia nos sintomas de ansiedade em universitários da área da saúde: uma revisão sistemática e metanálise - Santos, Anne Manuelle dos (2022)
Objective: To analyze the effectiveness of the practice of auriculotherapy on anxiety symptoms in university students in the health area. Method: This is a systematic review of a clinical trial with meta-analysis, conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. The searches were carried out in the Cumulative Index to Nursing and Allied Health (CINAHL), Cochrane Controlled Trials Register (Cochrane), U.S. National Library of Medicine (PubMed), a database that indexes international articles from the American Psychological Association – APA (PsycINFO), Virtual Health Library Americas Traditional, Complementary and Integrative Medicine (BVS TCIM), SCOPUS and Web of Science., in addition to the gray literature. Meta-analysis results were expressed as standardized mean difference (SMD), risk of bias was assessed by the “Cochrane Risk Of Bias Tool for randomized trials” and the quality of evidence by GRADE. The meta-analysis was performed in Review Manager. Result: Of the 961 articles selected, 7 studies were included in the meta-analysis. The overall sample size was 325, with 103 students for the intervention group when compared to the placebo group with 88, and 86 students for the intervention group when compared to 78 for the control group. When comparing the intervention group with the control group, it was observed that auriculotherapy has a significant impact on the reduction of anxiety symptoms SMD= 0.63; 95% CI (0.94 - 0.31), with no heterogeneity I2 0. When comparing the intervention group with placebo, the impact of the auriculotherapy effect was also significant in reducing MDS symptoms 0.85; 95% CI (1.21 - 0.49) heterogeneity was low to moderate I2 26%. The quality of evidence for both groups was considered moderate. Conclusion: Auriculotherapy is presented as a therapeutic practice option aimed at improving anxiety symptoms in university students in the health area. Although this study proves its effectiveness, it is still not clear which is the best auriculotherapy technique to reduce anxiety levels, which suggests further research in order to reinforce its strength of recommendation and consolidate this practice.